Adjuvant chemotherapy for colorectal cancer: age differences in factors influencing patients' treatment decisions - Jorgensen ML; Young JM; Solomon MJ (Patient Preference and Adherence, 2013)
Mikaela L Jorgensen,1,2 Jane M Young,1,2 Michael J Solomon1,31Surgical Outcomes Research Centre (SOuRCe), Sydney School of Public Health, University of Sydney and Sydney Local Health District, NSW, Australia; 2Cancer Epidemiology and Services Research (CESR), Sydney School of Public Health, University of Sydney, NSW, Australia; 3Discipline of Surgery, University of Sydney, NSW, AustraliaPurpose: Older colorectal cancer patients are significantly less likely than younger patients to receive guideline-recommended adjuvant chemotherapy. Previous research has indicated that patient refusal of treatment is a contributing factor. This study aimed to identify potential barriers to adjuvant chemotherapy use in older patients by examining the associations between patient age, factors influencing chemotherapy treatment decisions, and preferences for information and decision-making involvement.Patients and methods: Sixty-eight patients who underwent surgery for colorectal cancer in Sydney, Australia, within the previous 24 months completed a self-administered survey.Results: Fear of dying, health status, age, quality of life, and understanding treatment procedures and effects were significantly more important to older patients (aged ≥65 years) than younger patients in deciding whether to accept chemotherapy (all P < 0.05). Reducing the risk of cancer returning and physician trust were important factors for all patients. Practical barriers such as traveling for treatment and cost were rated lowest. Older patients preferred less information and involvement in treatment decision making than younger patients. However, 60% of the older group wanted detailed information about chemotherapy, and 83% wanted some involvement in decision making. Those preferring less information and involvement still rated many factors as important in their decision making, including understanding treatment procedures and effects.Conclusion: A range of factors appears to influence patients' chemotherapy decision making, including, but not limited to, survival benefits and treatment toxicity. For older patients, balancing the risks and benefits of treatment may be made more complex by the impact of emotional motivators, greater health concerns, and conflicts between their need for understanding and their information and decision-making preferences. Through greater understanding of perceived barriers to treatment and unique motivators for treatment choice, physicians may be better able to support older patients to make informed decisions about their care.Keywords: preferences, views, decision making, adjuvant therapy, older, elderly